Advanced Project 2007 - Miles, Timothy; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course covers the features within Microsoft Project 2007 that every project manager needs to know. This includes setting advanced task settings, entering overtime work and selecting the cost rate table. After this course, you will know how to import a project from a different Microsoft Office application, create your own custom tables and views, and then create a custom report to answer questions for management."--Resource description page.
Title from title screen.
Date of publication taken from resource description page (Safari, viewed May 16, 2013).
Presenter, Timothy Miles.
Keywords: Microsoft Project; Project management -- Computer programs; Electronic books